Histórias que vi e vivi: ficção, memórias e representações de uma educadora popular no romance Outros Cantos de Maria Valéria Rezende - Macau, Kedna Karla Ferreira da Silva (2019)
The present work entitled "Stories I have seen and lived: fiction, memories and representations of a popular educator in the novel Outros Cantos written by Maria Valéria Rezende”, had the general objective to understand the representations of Popular Education presented by the narrator Maria. Qualitative research in the field of the History of Education was supported by the theoretical-methodological reference of Cultural History. The novel Outros Cantos our main source, was analyzed in the interface with secondary sources: text of the writer of the work in study, that reflects on its conceptions of Popular Education, we also use media materials - printed interviews and audiovisual of the same, that are of public domain. It was in the relations established between memory-reality-fiction that the work Outros Cantos was analyzed. Therefore, with the analysis of the work, we conclude that the conceptions of Popular Education of Maria-narrator of the novel Outros Cantos, are constructed in the interweaving of facets - literary writer, popular educator and the feminine universe of Maria Valéria Rezende, which are related in work analyzed. This triad of singularities becomes inseparable in their literature, where this memory operates fundamentally in a double temporality, that is, in the movement between present and past. We try to understand its literary production from a double temporality, so we confirm our hypothesis that the work analyzed goes back to the experiences, or rather a "parenthesis" of the itinerary of his life, a period that precedes his literary writing in the years 2000, of the twentieth century, which means a retreat to the period of years of military dictatorship in Brazil. For this, we turn to memory studies based on Bosi (1994) for understanding that remembering is narrating, and narrating is remembering, so this is a process of historical resignification. We look for in Halbwachs (1990) his studies that deal with "social memory": being this one constituted by memories, that although starting from the singularity an individual, represent a collective memory. We continue with the studies of cultural representations Chartier (1990), because they understand that literary works are constituted by memories, memories, whose anchor are experiences, which bear witness to something that was lived, observed in their relations between the real and fiction. In this perspective, we are based on Pesavento (2003) for understanding that History and Literature represent different discourses of history, and has in common an imaginary. These authors, among other authors, have played a fundamental role in shaping our analyzes, as in Freire (1981), when we share their teachings that portray education as a process of political awareness. It was in the traces of memory evoked by the literary character that a popular educator revealed herself: Maria, inspired by the proposals of Paulo Freire, arrives in the village of the fictional name Olho d 'Água, to be a teacher of the Brazilian Movement of Literacy (Mobral), or rather, it was in the counterproposal of this literacy program that it sought to build an educational process committed to the political awareness of these subjects.